Steuerungswandel in der europäischen Umweltpolitik? - Katharina Holzinger; Christoph Knill; Ansgar Schäfer (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
– If one considers the different environmental action programs of the EU in which the strategic orientation of the EU environmental policy is defined for the mid-range, one can hardly avoid the impression that there has been a comprehensive transformation in the ideas about political governance. On the one hand, since the middle of the eighties, there has been an increasing demand to introduce economic instruments. On the other hand, especially since the beginning of the nineties, context-oriented governance approaches have been emphasized. Since both the middle of the eighties and the beginning of the nineties, a regulatory policy paradigm switch has been explicitly called for in the respective programs, expressed in the language of second generation instruments or new regulatory approaches. However, this transformation in the area of regulatory ideas is only partially reflected in changes in the concrete instruments that are used in the environmental policy legal acts of the EU. The discrepancy between the political declarations and action programs, on the one hand, and the actual decisions being made, on the other, is especially clear with respect to the economic instruments. But when measured in reference to the political demands, it also appears that relatively few context-oriented instruments have been introduced. Command-and-control instruments are still the dominant form of environmental policy governance in the EU.
Keywords: 330; Policy-Mix; EU-Staaten; EU-Umweltpolitik